Psychological preparation of the Cuban Powerlifting Team for the Parapanamerican Games Toronto 2015. (Original) (Revista científica Olimpia, 2024)
Disabled people in Cuba practice powerlifting and the results have increased with time, which is visible in the records obtained in national and international championships.  Granma Province has been the leader for four consecutive years, and for this reason the training of the weightlifting national team for the Parapanamerican Games Toronto 2015 was carried out in this province. The psychological preparation has been an important part during the training of the disabled athlete in the province. It was planned in the twomicrocycles established by the trainer for the Parapanamerican Games Toronto 2015. The main objectives were directed to diagnose the behavior and promote different psychic processes and personality traits that favor the sports performance in trainings and competitions, as well as to contribute to the improvement of techniques in the execution of the exercise. For this, the psychological performance inventory, the profile of moode state (POMS), goal establishment, performance self-control, breathing therapy, visualization,relaxation and rational psychotherapy were used. The investigation showed a decrease in self-valuation of error coefficient of athlete executions and contributed with the acquisition of their sport form and efficiency rise.
Keywords: psychological preparation; Parapanamerican; powerlifting; disability